Respuesta :

Answer:

There are two possible solutions for [tex]g(x)[/tex]:

[tex]g(x) = (x+3)^{2}-5[/tex]

[tex]g(x) = x^{2}-3\cdot x +4[/tex]

Step-by-step explanation:

From statement, we understand that [tex]g(x)[/tex] is defined by the following operation:

[tex]g(x) = f(x) +5[/tex] (1)

If we know that [tex]f(x) = (x+3)^{2}-10[/tex], then [tex]g(x)[/tex] is defined by:

[tex]g(x) = (x+3)^{2}-10+5[/tex]

[tex]g(x) = (x+3)^{2}-5[/tex]

[tex]g(x) = x^{2}-3\cdot x + 9 -5[/tex]

[tex]g(x) = x^{2}-3\cdot x +4[/tex]

Answer:

There are two possible solutions

Step-by-step explanation: